If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -13 = 4x + 2 Reorder the terms: -13 + 2x = 4x + 2 Reorder the terms: -13 + 2x = 2 + 4x Solving -13 + 2x = 2 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -13 + 2x + -4x = 2 + 4x + -4x Combine like terms: 2x + -4x = -2x -13 + -2x = 2 + 4x + -4x Combine like terms: 4x + -4x = 0 -13 + -2x = 2 + 0 -13 + -2x = 2 Add '13' to each side of the equation. -13 + 13 + -2x = 2 + 13 Combine like terms: -13 + 13 = 0 0 + -2x = 2 + 13 -2x = 2 + 13 Combine like terms: 2 + 13 = 15 -2x = 15 Divide each side by '-2'. x = -7.5 Simplifying x = -7.5
| 90+(2x-2)+x+5=180 | | 30x+25y=12551 | | 4/4-1/2= | | 10-2x=.5 | | x+(x+10)=15 | | 6/x-3/x=4 | | 3.2x+4.5x+3-2=-2.2x+5x-7 | | 5+x(x-4)=37 | | 4y+9x+3=7+9x | | 2y=y+10 | | 2e^3x+6=32 | | 15/15-12/12 | | 4p-2c-2p+8c= | | sen(5x)=0 | | 3x+2y=8.75 | | I-20=-23 | | 0=30x-16x^2 | | 23/24-11/12 | | 15x(8-5)= | | 6=n/2 | | 9x^2-3x+4=15-x | | 9x^2-3x+4=15x | | in(2x-5)+3=9 | | 16t^2-54t-7=0 | | n=3.75*4 | | 12=16t^2+24t+3 | | 2x^2-y^2=8solvey | | 16x^4+8x^2+3=0 | | 27+n=42 | | 2x^2+3x+1.125=0 | | -8n=120 | | 3x^2+27x=-18 |